1964
DOI: 10.1111/j.1365-2621.1964.tb01690.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes Occurring in the Pectinesterase Activity and Pectic Constituents of the Component Parts of Citrus Fruits II. Pineapple Orangesa

Abstract: SUMMARY Pectinesterase activity, 3 pectic fractions, and other characteristics were determined periodically on 5 component parts of Pineapple oranges during a 9.month maturation cycle for 2 seasons. Generally, PE activity was greatest in the peel, membrane, and juice sacs in March, April, and May, when the Brix/acid ratio was highest. However, the activity varied in similar components for like months during the 2 seasons. The order of component parts for PE in most cases, from highest to lowest activity, was j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

1967
1967
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 2 publications
0
8
1
1
Order By: Relevance
“…The results also would correlate well with the observation of Gee et al (1959) on the percent esterification of pectin ; i.e., PE activity was greatest in the immature pear where the percent esterification of pectin is lowest, whereas PE activity was minimal in the mature fruit where the percent esterification is greatest. These results differ from those obtained with oranges (Rouse et al, 1962(Rouse et al, , 1964 and bananas (Hultin and Levine, 1965). In oranges PE activity on a weight basis either remained constant or increased during maturation of the fruit.…”
Section: Whencontrasting
confidence: 79%
“…The results also would correlate well with the observation of Gee et al (1959) on the percent esterification of pectin ; i.e., PE activity was greatest in the immature pear where the percent esterification of pectin is lowest, whereas PE activity was minimal in the mature fruit where the percent esterification is greatest. These results differ from those obtained with oranges (Rouse et al, 1962(Rouse et al, , 1964 and bananas (Hultin and Levine, 1965). In oranges PE activity on a weight basis either remained constant or increased during maturation of the fruit.…”
Section: Whencontrasting
confidence: 79%
“…The different pectins were extracted using the method described by Rouse et al . and Majumder and Mazumdar with slight modifications.…”
Section: Methodsmentioning
confidence: 99%
“…The pectin contents were measured using the carbazole spectrophotometric method at an absorbance wavelength of 530 nm. The galacturonic acid curve for the standard sample was used to calculate the pectin content (g kg −1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main fractions of citrus polysaccharides are pectic substances, hemicelluloses, cellulose, and lignin (Ting 1980; Table 5). Individual hydrolysis of the pectin, hemicelluloses, and cellulose revealed that certain monosaccharides, such as arabinose and galactose, were discovered in all fractions, whereas free xylose primarily existed in the hemicellulose fraction, and galacturonic acid and glucose dominated the pectin and cellulose fractions (Ting and Deszyck 1961; Rouse and others 1962, 1964). Previously reported results, based on the assumption that each hydrolyzed product is derived from a homogeneous polysaccharide, suggested that orange and grapefruit peels consist of 7% to 10% araban, 5% to 6% galactan, 2.5% xylan, 15% to 28% cellulose glucosan, and 23% polygalacturonic acids, accounting for approximately 53% to 70% of the ethanol‐insoluble solids in the peel (Ting and Deszyck 1961).…”
Section: Macronutrientsmentioning
confidence: 99%